Penyuluhan Pentingnya Digital Marketing untuk UMKM - Rumy, Jalalludin; Kusumasari, Indah Respati (Jurnal Bisnis Indonesia, 2024)
Ngipik Subdistrict has potential, especially for UMKM whose management has not been optimal. Thisis caused and reflected by the intellectual level of the people who are educated below junior highschool and the majority of the residents of Ngipik sub-district work as laborers and some residentsown UMKM such as potato chips, presto milkfish, takoyaki and others. In improving their business,residents of Ngipik Subdistrict do not yet have knowledge regarding digital-based sales. Therefore, theaim of this service is to provide outreach regarding Digital Marketing for UMKM in the Ngipik subdistrict, Gresik Regency. The method used in this training activity is the lecture and discussionmethod. The lecture method is used by the presenter to explain the material related to material aboutdigital marketing. Next, a discussion was held to deepen the discussion material, both in the form ofquestions and answers individually and by participant representatives. The results of the serviceshowed very high enthusiasm from the participants who were UMKM players in the Ngipik subdistrict. This was shown by the many questions asked by the participants regarding the procedures forcreating accounts on the market place platform and the resource persons tried to answer thesequestions and provide explanations. in depth regarding the topic being asked.Keywords: Counseling; Digital Marketing; UMKM